AN ANALYTICAL-CRITICAL APPROACH TO HISTORICAL ITINERARY OF CRITICISM OF SKEPTICISM FROM IBN SINA TO MULLA SADRA - Miri, Seyyed Mohsen (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2013)
Surveying some Muslim philosophersâ€™ thoughts (from Ibn Sina to Mulla Sadra), this article attempts to indicated remarkable role of Islamic philosophy in intellectual confrontation with skepticism and expounds how much this tradition has been capable of enriching and deepening that discussion. This paper will also shows Ibn Sinaâ€™s pattern of proving possibility of knowledge and negating skepticism. Mulla Sadra who considered has been influenced by Ibn Sina, al-Razi, and Suhrawardi, in critizising of skepticism, he has dealt with this in his two works of HashÄ«yÄt ElÄhiyyÄt al-ShifÄâ€™ and al-AsfÄr al-ArbÄâ€˜a.